Analysis of Prolonged Pediatric Intensive Care Stay in Children with Diabetic Ketoacidosis - Singh, Sandip Kumar; Rijal, Shikha; Sah, Vijay Kumar; Khanal, Babita; Giri, Arun (Journal of Nobel Medical College, 2020)
Background: Diabetic ketoacidosis is one of most serious complication of diabetes requiring intensive care management. We aim to analyze various factors responsible for prolonged duration of stay in pediatric intensive care unit in a child with Diabetic Ketoacidosis. Materials and Methods: This was a hospital based prospective observational study conducted in Nobel Medical College and Teaching Hospital among children with Diabetic ketoacidosis over the period of one year. A total of 22 cases with Diabetic ketoacidosis aged 1 month to 18 years were included and clinical profile, laboratory reports including blood gas analysis were documented. Results: Among cases of Diabetic ketoacidosis, 4 (18%) cases were of mild Diabetic ketoacidosis, 4 cases (18%) were of moderate Diabetic ketoacidosis and 14 cases (64%) were of severe Diabetic ketoacidosis. Mean duration of Intensive care stay in new cases of Diabetic ketoacidosis was 69.46 hours which was significantly higher compared to old cases (30.66 hours) suggested by p value < 0.0001. In 15 cases (68%), acidosis resolved in less than 48-55 hours, whereas 7 cases (32%) required more than 48-55 hours for resolution of acidosis, hence required longer Intensive care stay. Cases who required prolonged Pediatric Intensive care stay, sepsis was contributing factor in 3 cases (42.85%), one case (14.28%) has associated muscular dystrophy and 3 cases (42.85%) had hyperchloremia at the end of 48 hours. Conclusion: Presence of sepsis and Hyperchloremia are important reasons for prolonged stay in Intensive Care Unit in Diabetic ketoacidosis patients. Other associated chronic illness can also prolong intensive care stay in Diabetic ketoacidosis patients.